In silico exploration of the potential barcode DNA in Anopheles sp., a malarian vector from Indonesia - Syubbanul Wathon; Devi Astikaningrum; Naura Paramitha Cindy Ardyah; Rike Oktarianti; Kartika Senjarini (Universitas Islam Negeri Sumatera Utara, 2023)
Malaria is an infectious disease caused by Plasmodium and transmitted to humans through the Anopheles mosquito vector. The large diversity of Anopheles in Indonesia, which consists of similar complex species, makes it difficult to identify species based on morphological characteristics. Therefore, it is necessary to have another approach to identifying species based on molecular characteristics using DNA molecular markers. This approach becomes important as a basis for vector-based malaria control efforts. This research aims to explore potential DNA barcodes based on in silico studies as a reference for DNA barcoding analysis of Anopheles species in Indonesia. The data sequences of CO1 and ITS2 from Anopheles sp. were collected on the NCBI database. The sequence alignment was performed using CLUSTALX2. The construction of a phylogenetic tree was carried out using MEGA XI. Data analysis was performed by observing the construction of phylogenetic trees, bootstrap scores, and genetic distance. The data sequence in NCBI shows that 10 species of the genus Anopheles as malaria vectors have been studied in Indonesia. Sequence alignment of the 10 species based on CO1 and ITS2 markers showed that ITS2 markers had higher genetic variation than CO1. Therefore, the ITS2 sequence has the potential to be a DNA barcode for the molecular identification of Anopheles.